(untitled) (Medical Forum Monthly, 2024)
Objectives: To present variations in renal arterial anatomy. To document renal artery number, source, course and patterns. Study Design: Observational / descriptive study. Place and Duration of Study: This study was conducted at the Angiography suite, Radiology Department, Sindh Institute of Urology and Transplantation from May 2011 to Oct 2011. Materials and Methods: A total of 100 healthy adultswho underwent renal angiography for renal donor assessment in living related transplant programwere included. Both male and female with age group between 20-50 years having normal clotting profile, renal function and normal morphology on IVP were fully evaluated by predesigned performa including number, source, course and pattern of renal artery. Results: Out of 100 cases of healthy renal donors, 66 were male and 34 were female. Fifty four percent were in 20 – 30 years of age group while 30% between 31 – 40 years and 16% in between 41 – 50 years. In 56% right renal artery found to be higher than left, where as 40% had both the arteries at same level. Right renal artery longer in 52% and left in 46%. Only 2% had same length of both renal arteries. Regarding the number, 66% had bilateral single, 24% unilateral double, 6% bilateral double and only 4 % unilateral triple. Out of 100 renal donors with 200 renal pedicles (each donor having 2kidneys ), single hilar artery seen in 75% in single hilum with inferior polar aortic branch in 14% and single hilar with suspicious polar aortic branch seen in only 4%. Double hilar arteries seen in 1% and hilar with extrahilar branch in 4% . Triple vessels found in 4% cases. Conclusion: The study shows that normal variation of vascular anatomy of renal pedicle is clinically very important to perform urological interventional procedures and transplantation. This study providesinformation concerning renal artery anatomy not only for interventional radiologists but also to urologic surgeon.